2019
DOI: 10.1016/j.nuclphysb.2019.114798
|View full text |Cite
|
Sign up to set email alerts
|

Integrable 2d sigma models: Quantum corrections to geometry from RG flow

Abstract: Classically integrable σ-models are known to be solutions of the 1-loop RG equations, or "Ricci flow", with only a few couplings running. In some of the simplest examples of integrable deformations we find that in order to preserve this property at 2 (and higher) loops the classical σ-model should be corrected by quantum counterterms. The pattern is similar to that of effective σ-models associated to gauged WZW theories. We consider in detail the examples of the η-deformation of S 2 ("sausage model") and H 2 ,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
90
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(95 citation statements)
references
References 70 publications
4
90
0
1
Order By: Relevance
“…Since these models can be thought of as a generalization of non-abelian T-duality [11,12,14] (which can be recovered in an appropriate η → ∞ limit) our findings suggest that the same should be true for NATD. This was also argued recently from a different perspective in [28,29], studying renormalizability of a different type of integrable deformation of σ-models. 20 To test this idea one should start from a model which is conformal to all orders in α ′ and then deform it.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Since these models can be thought of as a generalization of non-abelian T-duality [11,12,14] (which can be recovered in an appropriate η → ∞ limit) our findings suggest that the same should be true for NATD. This was also argued recently from a different perspective in [28,29], studying renormalizability of a different type of integrable deformation of σ-models. 20 To test this idea one should start from a model which is conformal to all orders in α ′ and then deform it.…”
Section: Discussionmentioning
confidence: 53%
“…Since the homogeneous YB deformations can be constructed using NATD, our results indicate that also NATD should preserve conformality at two loops, and possibly all orders in α ′ . Another piece of evidence for this comes from the recent analysis of renormalizability of deformed sigma models with two-dimensional target space in [28], and very recently [29]. Some of the deformations considered have a limit where they reduce to NATD and it was found that the models behave nicely beyond lowest order in α ′ suggesting that things should work out to all orders in α ′ .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This question of higher loop orders was addressed recently in [3], where we showed that, starting from 2 loops, renormalizability requires a specific deformation of the classical target space geometry, which may be interpreted as the result of adding finite local counterterms.…”
Section: Introductionmentioning
confidence: 95%
“…The two-loop RG equation of this model was also recently considered in[44]. The background metric was modified by a quantum correction (determinant) arising from the integration of the gauge fields.…”
mentioning
confidence: 99%